ByzRev 06.2024.065: Neil Churchill, Power and Representation in Byzantium: The Forging of the Macedonian Dynasty: (Studies in Byzantine Cultural History). London – New York: Routledge 2024. - Signes Codoñer, Juan (The Byzantine Review, 2024)
Neil Churchill, Power and Representation in Byzantium: The Forging of the Macedonian Dynasty (Studies in Byzantine Cultural History). London – New York: Routledge 2024. 265 pp. – ISBN 978-1-003-25529-1